2004
DOI: 10.1074/jbc.m403363200
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization of the β2-Adrenergic Receptor as a Prerequisite for Cell Surface Targeting

Abstract: Although homodimerization has been demonstrated for a large number of G protein-coupled receptors (GPCRs), no general role has been attributed to this process. Because it is known that oligomerization plays a key role in the quality control and endoplasmic reticulum (ER) export of many proteins, we sought to determine if homodimerization could play such a role in GPCR biogenesis. Using the ␤2-adrenergic receptor (␤2AR) as a model, cell fractionation studies revealed that receptor homodimerization is an event o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
229
4
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(242 citation statements)
references
References 51 publications
7
229
4
2
Order By: Relevance
“…Indeed, receptor dimerization can occur in the ER (Smith and Milligan, 2010;Dupré et al, 2012). Mutagenesis studies targeting the putative interaction interface of β 2 -adrenergic receptor showed that inhibiting β 2 dimerization caused its retention in the ER, thus supporting the hypothesis of receptor oligomerization in this cellular compartment (Salahpour et al, 2004). Other examples encompass the D 4 receptors (Van Craenenbroeck et al, 2011), GABA B receptors (MargetaMitrovic et al, 2000), and 5-HT 2C receptors (Herrick-Davis et al, 2006).…”
Section: Role Of Endoplasmic Reticulum (Er) and Chaperonesmentioning
confidence: 86%
“…Indeed, receptor dimerization can occur in the ER (Smith and Milligan, 2010;Dupré et al, 2012). Mutagenesis studies targeting the putative interaction interface of β 2 -adrenergic receptor showed that inhibiting β 2 dimerization caused its retention in the ER, thus supporting the hypothesis of receptor oligomerization in this cellular compartment (Salahpour et al, 2004). Other examples encompass the D 4 receptors (Van Craenenbroeck et al, 2011), GABA B receptors (MargetaMitrovic et al, 2000), and 5-HT 2C receptors (Herrick-Davis et al, 2006).…”
Section: Role Of Endoplasmic Reticulum (Er) and Chaperonesmentioning
confidence: 86%
“…Therefore, dimers are unable to export from the ER. Dimerization has been well described for a variety of G protein-coupled receptors [9][10][11][12][13][14][15][34][35][36][37][38][39][40][41]. However, whether α 2B -AR is capable of forming homodimers has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, AT1R-GFP was not found in the anti-HA immunoprecipitate when co-expressed with HA-α 2B -AR. These data indicate that HA-and GFP-tagged α 2B -AR or α 2B -ARm were co-immunoprecipitated as a complex and suggest that α 2B -AR as well as α 2B -ARm underwent homodimerization, similar to many other G protein-coupled receptors [9][10][11][12][13][14][15].…”
Section: Homodimerization and Heterodimerization Of α 2b -Ar And α 2bmentioning
confidence: 91%
See 1 more Smart Citation
“…With respect to the latter, a series of studies that have asked when and where in the cell newly-synthesized receptor monomers associate has led to the conclusion that oligomerization is a prerequisite for receptor maturation and plasma membrane sorting (14,22,23). These findings pertain mostly to the more well-studied family A GPCRs, and even in those cases only the most interesting or functionally relevant receptor domains have been evaluated for their effects on oligomerization and sorting.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%